BUM Desa; Antara Fungsi Profit dan Sosial (Studi Kasus BUM Desa Swadesa Arta Mandiri, Lampung Selatan - Ridwan Saifuddin (Balitbangda Provinsi Lampung, 2019)
This research explores BUM Desa business process, to find out the BUM Desa business practices which are considered to perform well in Lampung Province, as financial profit oriented economic institutions as well as social oriented,, with descriptive qualitative research methods. Profile of BUM Desa that was appointed in this study was BUM Desa Swadesa Arta Mandiri, Wonomarto Village, North Lampung Regency, which has several business units, such as managing water tourism, trade, village markets, waste management, and financial institutions. Ideally, the two functions of BUM Desa as profit institutions and social institutions can work synergistically. The ability of BUM Desa managers to integrate social and profit functions well, will give birth to a more optimal institutional performance in providing economic and social benefits to the village community. The concept of social entrepreneurship is good for development by BUM Desa managers. The measure of the success of BUM Desa is not merely in the form of money profits, but rather in its ability to move and dynamize the wheels of the village economy, so as to increase the economic capacity of its citizens